Análise do composto de marketing no segmento varejista de padarias: um estudo em Natal-RN. - Praxedes, Karenina da Silva Santana (2007)
Recent transformation in the business world has caused significant changes in products merchandising. In the retail division, there has been no difference. Due to stabilization of economy and by opening the market to international companies, important retailers were threatened by a new store configuration and by increasing the small retail division. This change demanded a new competitive approach from stores. In order to achieve this goal, companies developed a marketing plan to satisfy the customers' desires, expectative and needs. Therefore, the research aimed to analyze the retail marketing process used by small bakeries in the city of Natal RN. The point was to identify whether or not the adopted strategies were noticed by managers and customers in the same manner. The research also looked for general information about consumer satisfaction related to the marketing plan and about administrative issues, by associating the variables. As far as methodology is concerned, the study used a quantitative approach, with an exploratory, descriptive focus. The results were possible through a bibliographic and field research. Data were collected by means of a field research with managers and customers chosen for the study. The sample consisted of bakeries with a profile in SINDIPAN-RN (Union of Industry of Bakeries and Candy Stores in Natal RN). The type of sample used was the non-probabilistic for the managers as much as for the researcher. The data collection was done through interviews that used a questionnaire with structured and non structured questions. Later, computer programs took care of computing data analysis. Through the research, it was possible to point out different opinions, having both audiences investigated, regarding products, services, cost, location, clearance and layout. The research also categorized different responses in management aspects such as: action plan, use of research tools to control products sales, partnership with vendors to establish product cost, marketing action plan, awareness of ranking in the market, and use of consulting services and management consultantship. The research also showed that customers are less satisfied with services, such as products cost and sales and that the company's action plan is directed related to the education background of the managers.